The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3329/bjm.v32i0.28475
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Alternative Enzyme-assisted Dehairing Method of Animal Skins using Proteases from Bacillus licheniformis MZK05M9

Abstract: The present study was aimed to develop an enzyme assisted dehairing method as an alternative and ecofriendly technique to reduce the use of harsh chemicals in leather manufacturing. For this purpose, two proteases namely alkaline protease (601 U/ml) and keratinase (132 U/ml) were produced by Bacillus licheniformis MZK05M9 (BlM9) in Soya molasses medium and Feather mill medium respectively, in 7.0 L bioreactor at pH 7.5 and 37°C. The cell free enzyme preparations were used together at 2.5% level in dehairing ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A mixture of lipase and protease, keratinase and Protease and amylase and protease enzymes had 100% complete unhairing but the resulting pelts were very soft. A similar study by Mamun et al, (2015), found that a mixture of 2.5% of keratinase and 2.5% of protease enzymes were able to unhair 85% of the pelt area for a period of 26 hours. The addition of calcium oxide to keratinase and protease enzymes improved the performance of the enzymes and the pelt area was unhaired 100% for a period of 24 hours (Mamun et al, 2015).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…A mixture of lipase and protease, keratinase and Protease and amylase and protease enzymes had 100% complete unhairing but the resulting pelts were very soft. A similar study by Mamun et al, (2015), found that a mixture of 2.5% of keratinase and 2.5% of protease enzymes were able to unhair 85% of the pelt area for a period of 26 hours. The addition of calcium oxide to keratinase and protease enzymes improved the performance of the enzymes and the pelt area was unhaired 100% for a period of 24 hours (Mamun et al, 2015).…”
Section: Resultsmentioning
confidence: 72%
“…A similar study by Mamun et al, (2015), found that a mixture of 2.5% of keratinase and 2.5% of protease enzymes were able to unhair 85% of the pelt area for a period of 26 hours. The addition of calcium oxide to keratinase and protease enzymes improved the performance of the enzymes and the pelt area was unhaired 100% for a period of 24 hours (Mamun et al, 2015). Several formulations gave a complete unhairing as indicated in Table 3.…”
Section: Resultsmentioning
confidence: 72%
“…With a view to increasing the performance, the bacterium was subjected to random mutagenesis using both chemical (ethyl methane sulfonate) and UV radiation 18 that eventually generated a mutant strain, B. subtilis M9 from a selection of potential strains, able to produce more efficient extracellular protease than that of the wild type. This was demonstrated in unhairing and bating of skin and hides, a performance comparable to that of the commercial enzymes, thereafter was applied successfully in leather industries 19 , 20 , 21 . Therefore, we attempted here to compare the genome sequencing of the two strains to pinpoint the probable cause of high-level expression of serine proteases in B. subtilis M9 mutant, the number of proteases, and other industrially useful enzymes and metabolites, genes responsible for extracellular protease secretion, genome variation in between the strains studied here with that of strains from different countries of origin, and evolutionary relationships present with other bacterial species of Bacillus subtilis group.…”
Section: Introductionmentioning
confidence: 87%